The interface between international trade and investment agreements and food environment policymaking: A conceptual framework - Garton, Kelly; Swinburn, Boyd; Thow, Anne Marie (Frontiers in Political Science, 2022)
Addressing the global challenge of malnutrition in all its forms will require policy measures to improve food environments, yet progress has been patchy and often slow, particularly for regulatory measures. International trade and investment agreements (TIAs) may limit governments’ ‘policy space’ for public health regulation. Constraints have been particularly apparent for public health measures targeting unhealthy commodities, including ultra-processed foods. Challenges and disputes regarding food environment regulation under TIAs (even if successfully defended) can entail significant drain of human and financial resources, and political capital. Lack of awareness or understanding of the implication of TIAs on policy space for regulation can contribute to regulatory chill and policy inertia. Governments lacking capacity to interpret their ‘legally available’ policy space may want to err on the side of caution when there is perceived risk of a formal dispute – even if such threats are unfounded. This paper draws on analysis of literature, trade and investment dispute documentation, and data from inter-disciplinary expert interviews (n=22) to present a new conceptual framework for the potential impacts of TIAs on policy space for regulating food environments. The analysis that underpins the framework focusses on the key policy domains of fiscal policies, front-of-pack nutrition labelling, restrictions on marketing to children, nutrient limits, and product bans. Analysis indicates that regulatory context and stakeholder influence, policy design, and mechanisms associated with TIA rules and provisions intersect in ways contributing to policy space outcomes. This new framework can provide a basis for rapidly assessing policy coherence between TIAs and food environment regulations in these domains. It can also be used to identify areas where further legal analysis would strengthen the development and defence of regulatory proposals. The framework may be applied to nutrition regulation more broadly, given the common themes that emerged across the different domains due to common interests of stakeholders, notably the food industry. It thus provides a basis for analysing the political economy of regulation to address the commercial determinants of health in relation to unhealthy food and beverages.